The role of Mycobacterium tuberculosis exosomal miRNAs in host pathogen cross-talk as diagnostic and therapeutic biomarkers - Mukhtar, Farwa; Guarnieri, Antonio; Brancazio, Natasha; Falcone, Marilina; Di Naro, Maria; Azeem, Muhammad; Zubair, Muhammad; Nicolosi, Daria; Di Marco, Roberto; Petronio Petronio, Giulio (Frontiers in Microbiology, 2024)
Tuberculosis (TB) is a threat that is claimed to be a global health phenomenon with a prevalence rate of one-quarter of the world's population. The World Health Organisation (WHO) also describes that 6 million people die annually due to chronic illnesses. This is attributed to factors such as the emergence of drug-resistant strains and the outstanding survival factors of Mycobacterium tuberculosis (MTB). However, miRNAs have lately come into focus for their exceptional role in TB pathogenesis compared to typical small RNAs (sRNA) since they can shift the immune facets of the host. For instance, miR-155, miR-125b, and miR-29a have been identified as effectors in the immune response to MTB regarding the modulation of macrophages and T cells and cytokine production. While sRNAs are constrained within cells, exo-miRNAs are secreted from MTB-infected macrophages, and the latter changes the function of cells to the benefit of the bacterium and continues the infection cycle. Other potential significance are that the expression of these miRNAs affects specific genes and pathways involved in immune functions, implying that they can be used to diagnose TB and as therapeutic targets. This kind of review, therefore, compiles existing information on the immunomodulatory function of exosomal miRNAs from MTB, particularly about the disease progression and scientific potential of this approach compared to the existing diagnostic techniques. Thus, to understand the focus of the role of exosomal miRNAs in TB and to know their potential for developing novel diagnostic and therapeutic methods.